Rheological characterization and prediction model of compressed air Class A foam. Issue 7 (1st June 2022) - Fan, Yuyan; Wang, Yongkai; Gao, Hong; Lin, Quansheng; Song, Bo; Xia, Jianjun
Abstract: When the compressed air Class A foam used in firefighting covers the surface of the object, free drainage and changes of structural occur. The evolution of the foam and the law of drainage and rheological properties were investigated. It was observed by experiments that the evolution of the foam structure was consistent with the drainage process in terms of the time nodes division at room temperature. The foam evolved from a spherical structure to an ellipsoidal structure at about 900 s, began to evolve toward a polygonal structure at 3000 s, and eventually became a polygonal structure at 3600 s. At the same time, the foam drainage mass rate can be divided into three stages: increasing stage (300–900 s), dropping stage (900–3000 s), and stabilizing stage (3000–3600 s). The similarity of the time nodes determines the interaction between the two phenomena. At room temperature, when the liquid volume fraction is between 0.03 and 0.14, a linear relationship between the foam yield stress and the liquid volume fraction could be established. Furthermore, the Herschel–Bulkley model was modified by introducing a structural damage factor λ ( t ) to describe the change in foam rheological properties over time. Graphical Abstract: